2010
DOI: 10.1111/j.1752-248x.2010.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the radiological predictive factors of inferior alveolar nerve injury with cone beam computed tomography findings

Abstract: Aim:  This study assessed the radiological signs considered predictive of inferior alveolar nerve (IAN) injury and correlated them with findings from cone beam computed tomography (CBCT). Material and methods:  This was a prospective study of patients who underwent CBCT scanning of mandibular third molars when panoramic radiographs indicated an ‘increased risk’ of IAN injury during extraction. Results:  Seventy‐eight per cent of the teeth identified showed darkening across the root. Thinning or perforation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 19 publications
2
37
2
4
Order By: Relevance
“…1 The reported incidence varies widely. 2 To discover the relation between the nerve and the tooth, standard preoperative evaluation relies on panoramic imaging, and two-dimensional images may be examined for signs indicative of increased risk of damage to the nerve. 3 It is generally accepted that unless the root of a mandibular third molar appears on the radiograph to lie in close proximity to, or to overlap the inferior alveolar canal, there is little (if any) physical risk to the nerve; but surgical risk, which depends on the operator and the technique, 4 should also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…1 The reported incidence varies widely. 2 To discover the relation between the nerve and the tooth, standard preoperative evaluation relies on panoramic imaging, and two-dimensional images may be examined for signs indicative of increased risk of damage to the nerve. 3 It is generally accepted that unless the root of a mandibular third molar appears on the radiograph to lie in close proximity to, or to overlap the inferior alveolar canal, there is little (if any) physical risk to the nerve; but surgical risk, which depends on the operator and the technique, 4 should also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…12, 13 In another study, it was found that loss of radiopaque border and deviation of canal was an indicator of contact with the canal and increased risk of inferior alveolar nerve injury. 5 The findings of CBCT was encouraging in detecting anatomical position of inferior alveolar canal and impacted mandibular third molar tooth and is definitely superior to orthopantomogram. Therefore, CBCT is a promising test in preoperative assessment of impacted mandibular third molar position and inferior alveolar canal.…”
Section: Discussionmentioning
confidence: 82%
“…4 Radiographic signs include-root darkening, roots deflection, root narrowing, dark and bifid root, interruption of the white line, diversion and narrowing of the of inferior alveolar canal. 5 However, opinion regarding the frequencies of the above mentioned signs for predicting the inferior alveolar nerve position or clinical complications such as paraesthesia after removal of mandibular third molar. If the panaromic radiographs indicates there is a close relationship between the third molar and the mandibular canal, supplement investigation using CT may be recommended to verify.…”
Section: Introductionmentioning
confidence: 99%
“…15 Umar et al reviewed 50 cases that had been identified as high risk on plain films and then correlated the CBCT findings with their appearance. Loss of lamina dura of the canal was linked to contact with the canal in all cases, darkening was related to canal cortical loss in 78% of cases, contact with the nerve in 60% and grooving of the root in one case.…”
Section: Radiographymentioning
confidence: 99%